Indigenous participation in Australian economies Historical and anthropological perspectives - Keen, Ian (ANU Press, 2010)
This volume seeks to contribute to the body of anthropological and historical studies of Indigenous participation in the Australian colonial and post colonial economy. It arises out of a panel on this topic at the annual conference of the Australian Anthropological Society, held jointly with the British and New Zealand anthropological associations in Auckland in December 2008. The panel was organised in conjunction with an Australian Research Council (ARC) Linkage Grant project on Indigenous participation in Australian economies involving the National Museum of Australia as the partner organisation and the School of Archaeology and Anthropology at The Australian National University. The chapters of the volume bring new theoretical analyses and empirical data to bear on a continuing discussion about the variety of ways in which Indigenous people in Australia have been engaged in the colonial and post-colonial economy. Contributions cover settler capitalism, concepts of property on the frontier, Torres Strait Islanders in the mainland economy, the pastoral industry in the Kimberley, doggers in the Western Desert, bean and pea picking on the South Coast of New South Wales, attitudes to employment in general in western New South Wales, relations of Aboriginal people to mining in the Pilbara, and relations with the uranium mine and Kakadu National Park in the Top End. The chapters also contribute to discussions about theoretical and analytical frameworks relevant to these kinds of contexts and bring critical perspectives to bear on current issues of development.